2020
DOI: 10.1101/2020.06.26.170043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Normal mammary epithelia accumulate DNA methylation changes with age that are consistent with breast cancer methylomes

Abstract: The aging process is characterized by an accumulation of cellular damage, including alterations to the epigenome. While it is clear that DNA methylation patterns change with age, the mechanisms behind these epigenomic alterations - and their functional consequences - have remained unclear. One of the primary roles of DNA methylation in mammalian genomes is in the repression of retrotransposons. Many of these repetitive elements contain regulatory sequences, and loss of repression can lead to aberrant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 124 publications
(365 reference statements)
2
2
0
Order By: Relevance
“…p < 0.005, adj. p < 0.1) and was highly enriched in DMRs that were hypomethylated in the older cells ( Figures S3Li-ii), supporting our earlier findings based on a more limited set of whole genome bisulfite sequencing (WGBS) data in LEPs [Senapati et al, 2020].…”
Section: These Molecular Changes Recapitulated Previous Phenotypic Obsupporting
confidence: 88%
See 2 more Smart Citations
“…p < 0.005, adj. p < 0.1) and was highly enriched in DMRs that were hypomethylated in the older cells ( Figures S3Li-ii), supporting our earlier findings based on a more limited set of whole genome bisulfite sequencing (WGBS) data in LEPs [Senapati et al, 2020].…”
Section: These Molecular Changes Recapitulated Previous Phenotypic Obsupporting
confidence: 88%
“…Hypomethylation of this CpG island region in older LEPs was confirmed in our WGBS dataset [Senapati et al, 2020] (Figure S7Hi). This 5-CpG DMR was located in the first intron ( Figure S7Hi), a region that has been shown to have inverse correlation between intron methylation and gene expression [Anastasiadi et al, 2018].…”
Section: Dnam Changessupporting
confidence: 60%
See 1 more Smart Citation
“…Epithelial tissue within the breast shows maturo-developmental plasticity that supports lactational function. It was recently reported that over the course of time during adulthood, the methylome of healthy proliferating breast epithelial tissues increasingly resembles that of breast cancer (Sayaman et al, 2022;Senapati et al, 2022). This is a potential example of a maturo-developmental process displaying AP.…”
Section: Onto-developmental Fidelity Vs Maturo-developmental Plasticity?mentioning
confidence: 93%